Smart Wifi Plug Untuk Penghematan Energi Kipas Angin Di Asarma PTDI-STTD - Rendy Moh. Rizki Djula; Dita Rama Insiyanda; Elena Martiza W. Putri; Amin N. Huda; M. Raffi E.; Ihsan Fikrul; Ferdinand D. Gesar; Fathan N. Sandekala (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Electricity consumption in educational settings is often inefficient, especially in student dormitories where appliances such as fans are often left on even when the rooms are unoccupied. This behavior results in significant energy waste and increased utility costs. In accordance with Presidential Instruction No. 1 of 2025, which emphasizes strict budget efficiency, this study explores the impact of Smart WiFi Plug technology on reducing electricity usage and operational costs in PTDI-STTD dormitories. The study involved collecting data on fan power ratings, monitoring daily usage before and after implementation, and calculating electricity consumption using the kilowatt-hour formula. The findings revealed a 30% reduction in electricity usage, with monthly costs decreasing from Rp22,500 to Rp15,750 per fan, resulting in annual savings of Rp73,872,000. This demonstrates that Internet of Things (IoT)-based technology can significantly enhance energy efficiency through remote control and scheduled device operation. These results highlight the potential for broader adoption of smart energy solutions in other educational institutions. Keywords: Energy efficiency, Smart WiFi Plug, Internet of Things, dormitory management, electricity cost reduction